2018
DOI: 10.1002/ijgo.12563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise and dietary habits on the occurrence of polycystic ovary syndrome over 5 years of follow‐up

Abstract: Previous exercise habits were associated with subsequent PCOS whereas a recently acquired exercise routine was not. Women should avoid long-term sedentary lifestyle habits and focus on adding to the duration of, or enhancing the intensity of, physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…42 A few studies reported no variation in physical activity levels among PCOS cases and controls, which could be a result of modification in the activity, a learned behaviour, after receiving advice from doctors or healthcare workers. 26,29,43 The results of the present study support the previous findings indicating that unhealthy eating habits such as excess sugar and low protein are important risk factors for PCOS. 23 Crude dietary fibre exhibited a significant protective effect against PCOS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…42 A few studies reported no variation in physical activity levels among PCOS cases and controls, which could be a result of modification in the activity, a learned behaviour, after receiving advice from doctors or healthcare workers. 26,29,43 The results of the present study support the previous findings indicating that unhealthy eating habits such as excess sugar and low protein are important risk factors for PCOS. 23 Crude dietary fibre exhibited a significant protective effect against PCOS.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, as little as 5% weight loss is said to improve the reproductive, androgenic and metabolic profile of PCOS patients 42 . A few studies reported no variation in physical activity levels among PCOS cases and controls, which could be a result of modification in the activity, a learned behaviour, after receiving advice from doctors or healthcare workers 26,29,43 …”
Section: Discussionmentioning
confidence: 99%
“…A significant difference was found between cases and controls in performing daily low levels of activity and a dietary intake with vitamin insufficiency. Similarly, in another nested case–control study, women with PCOS were found to be less physically active ( p < 0.05) in their daily lives than healthy controls [ 28 ]. Women with PCOS were found to be less involved in sporting activities and reported to have a sedentary lifestyle, which can further lead to the development of metabolic syndrome [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is well accepted that adequate calorie restriction improves human health [5][6][7], whereas excess dieting is also known to induce several gynecological disorders such as dysmenorrhea and irregular menstruation [8,9]. It was also reported that dietary behaviors are closely related to the onset or management of polycystic ovary syndrome [10,11] and hypothalamic amenorrhea [12,13], suggesting the close relationship between gynecological disorders and dietary habits [14]. Furthermore, it was proposed that gynecologic diseases such as endometriosis, which are frequently manifested by dysmenorrhea, can latently develop with a common modern dietary lifestyle [15].…”
Section: Introductionmentioning
confidence: 99%